Growth and yield performance of local T Aman genotypes in southern region of Bangladesh - Howlader, MHK; Rasel, M; Ahmed, MS; Hasan, MM; Banu, LA (Progressive Agriculture, 2017)
The present experiment was conducted at the Research Field Laboratory of the Department of Agricultural Botany, Patuakhali Science and Technology University (PSTU), Patuakhali during the period from July to December 2013 to evaluate among the local T Aman rice genotypes for obtaining the most productive genotype regarding growth and yield performance under southern region. Four local T Aman rice genotypes namely Lalchicon, Lalmota, Moulata and Mothamota were used as planting materials and laid out in RCBD with three replications. The genotype Moulata was produced significantly the tallest plant (155.0 cm) and number of total tillers per hill (11.80); statistically higher LAI (2.133) and TDM (16.80 g hill1) at vegetative stage (60 DAT). Similarly, number of maximum effective and minimum non-effective tillers per hill (10.80 and 1.333), total and filled grains panicle1(128.50 and 115.80), minimum unfilled grains panicle (12.67), thousand grain weight (25.35 g), grain, straw and biological yield (3.657, 6.000 and 9.657 t ha1 respectively) and HI (37.86%)also higher in Moulata at harvest. So, Moulata was the most productive genotype among the studied local T Aman rice genotypes under the southern region. Progressive Agriculture 28 (2): 109-113, 2017